A Method of Transoral Finger Dissection for a Giant Epiglottic Lipoma - Toshizo Koizumi; Katsunari Yane; Toshiaki Yamanaka; Tadashi Kitahara (Case Reports in Otolaryngology)
Background. Subcutaneous lipomas that occur in the trunk and proximal extremities are commonly dissected by low-invasive method. However, a standard surgical method for lipomas of the epiglottis has been absent. Microscopic laryngeal surgery is appropriate to extirpate small epiglottic lipomas. However, microscopic laryngeal surgery may be insufficient for giant epiglottic lipomas because there is restricted visualization of the operating field of the tumor under the microscope. Furthermore, microscopic surgical instruments are very small to manipulate giant lipomas, and it would be excessive to approach these lipomas via external cervical incisions. Case Presentation. A 57-year-old female presented with a giant lipoma on the lingual surface of the epiglottis. Following a tracheotomy, microscopic surgery was inadequate to manipulate the epiglottic lipoma. Instead, we performed macroscopic surgery in which the epiglottic lipoma was pulled into the oral cavity with forceps and then separated from the surrounding tissues using the surgeon’s finger to dissect the tumor en bloc. Conclusion. The low-invasive method of transoral finger dissection enabled the giant lipoma to be extirpated without leaving any remnants or causing excessive epiglottic damage.